A breakdown of residual wage inequality in Germany - Philipp Ehrl (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2014)
The present paper applies several regression-based decomposition methods to analyze the impact of region-, worker-, irm- and sector-speciic determinants on the wage level and the continuous increase in wage inequality between 1995 and 2007 in Germany. In contrast to prior studies, more than 50% of the wage dispersion and almost the entire increase in wage inequality are explained in this approach. Altogether, the entire growth of wage dispersion occurs within regions and changes in the composition of wage determinants are minor compared to changes in their returns. I find that occupational attributes are the most important wage determinant. Changes in the firm size premium in combination with assortative matching also depress wages in the bottom of the distribution while they increase wages at the top. Workers with an unemployment record or an occupation in the service, construction and logistics sectors particularly experience falling wages.
Keywords: J31; J24; R12; 330; wage inequality; skill biased technical change; inequality decompositions